The relationship between transformational leadership and job performance: an empirical investigation - Muhammad Shah, Syed Mir; Abdul Majid, Abdul Halim; Samo, Altaf Hussain; Memon, Pervaiz Ahmed (Sukkur Institute of Business Administration, 2016)
The main objective of the present paper is to assess the relationship between transformational leadership and job performance empirically.The study was conducted in the banking sector of Pakistan focusing on six large banks.A total number of 308 responses were collected through survey questionnaire from the bank managers.The data was then coded into SPSS for early stage analysis such as data screening.This was followed through applying SmartPLS to analyze the data and the results have been presented in its standard reporting style.The findings revealed a positive relationship between transformational leadership and job performance in banking sector of Pakistan supporting the hypothesized relationship.Finally, the paper has presented a way forward for future research.